Effect of basalt fiber inclusion on the mechanical properties and microstructure of cement-solidified kaolinite. (30th April 2020) - Wang, Dongxing; Wang, Hongwei; Larsson, Stefan; Benzerzour, Mahfoud; Maherzi, Walid; Amar, Mouhamadou
Highlights: Eco-friendly & biologically inactive basalt fiber is chosen to improve cemented clay. Basalt fiber enhances ductility, UCS and peak deviatoric stress of cemented clay. Optimal amount of basalt fiber is identified for UCS and triaxial shear behaviour. Bridging of basalt fiber & cementing of hydration product makes a great contribution. Interface interaction between basalt fiber and cemented matrix is main mechanism. Abstract: The polypropylene fibers, which are currently attracting enormous attention in various geotechnical applications, carry a risk of aging under an integrated effect of heat, oxygen, light and other environmental factors, causing potentially infrastructure failure. An eco-friendly and biologically inactive material – basalt fiber, which has excellent natural resistance to aging and can eliminate aging-associated disasters, deserves more attention in geotechnical field. However, quite few studies are available on the beneficial reuse of basalt fibers to improve the engineering performance of soils. Therefore, this study aims to incorporate the sustainable basalt fiber and clarify how its inclusion impacts the mechanical properties and microstructure of cemented kaolinite. The experimental programs are comprised of three types of tests, i.e. two to examine the compressive strength and triaxial shear behavior and one to evaluate the microstructure properties. The results indicate that the basalt fiber reinforcement plays an essential role in enhancing the compressive strength and peak deviatoric stress of cemented and uncemented kaolinite. The inclusion of basalt fibers improves the ductility and weakens the brittleness of cemented kaolinite. The compressive strength increases with basalt fiber content and curing time, and reaches the peak at the fiber content of 0.2%, followed by a reduction due to the formation of weak zone at higher fiber content. The peak deviatoric stress is elevated until reaching the maximum at the basalt fiber content of 0.4%, after which further addition of basalt fiber tends to reduce its reinforcing effect. The peak deviatoric stress increases as the basalt fiber length is shortened and the confining pressure is raised. The strength gain of cement-basalt fiber inclusion is much more than the sum of strength increase induced by them individually. The combination of basalt fiber and cement has the virtues of both cement-stabilized and basalt fiber-reinforced kaolinite. The SEM analysis reveals that the mechanical interaction in the form of interface bonding and friction between kaolinite particle, cement hydration product and basalt fiber is the dominant mechanism controlling the reinforcement-cementation benefits. The bridging effect (reinforcement) of basalt fibers and binding effect (cementation) of hydration products make a major contribution to the formation of stable and interconnected microstructure, which results in an evident improvement in the mechanical behaviour of cemented kaolinite. The combination of basalt fiber and cement stabilization would be an innovative and effective method for geotechnical engineering works such as soft ground improvement.